2014
DOI: 10.1155/2014/780816
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-Weighted Magnetic Resonance Diagnosis of Local Recurrences of Prostate Cancer after Radical Prostatectomy: Preliminary Evaluation on Twenty-Seven Cases

Abstract: Objectives. To assess the diagnostic performance of diffusion-weighted MR imaging (DWI) in patients affected by prostatic fossa (PF) relapse after radical prostatectomy (RP) for prostatic carcinoma (PC). Methods. Twenty-seven patients showing a nodular lesion in the PF at T2-weighted MR imaging after RP, with diagnosis of PC relapse established by biopsy or PSA determinations, were investigated by DWI. Two readers evaluated the DWI results in consensus and the apparent diffusion coefficient (ADC) of the nodule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 31 publications
0
9
1
Order By: Relevance
“…In our study, for similar combinations (maximum b-values between 500 and 1100 s/mm 2 combined with b = 0 s/mm 2 ), the range of ADC values for PCa was equivalent (1.01-1.32 × 10 − 3 mm 2 /s). However, for both areas of normal glandular tissue (PZ and CG), the range and mean ADC values were lower than those previously reported [8,13,16,17,19].…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…In our study, for similar combinations (maximum b-values between 500 and 1100 s/mm 2 combined with b = 0 s/mm 2 ), the range of ADC values for PCa was equivalent (1.01-1.32 × 10 − 3 mm 2 /s). However, for both areas of normal glandular tissue (PZ and CG), the range and mean ADC values were lower than those previously reported [8,13,16,17,19].…”
Section: Discussioncontrasting
confidence: 79%
“…Our results demonstrate that PCa and normal tissue ADC values vary substantially with b-value combinations, in agreement with other studies. Previous ADC quantification studies used maximum b-values from 400 to 1000 s/mm 2 combined with b = 0 s/mm 2 , reporting ADC in PCa between 0.71 and 1.87 × 10 − 3 mm 2 /s and 1.03-3.71 × 10 − 3 mm 2 /s in healthy tissue [8,13,16,17,[19][20][21]. In our study, for similar combinations (maximum b-values between 500 and 1100 s/mm 2 combined with b = 0 s/mm 2 ), the range of ADC values for PCa was equivalent (1.01-1.32 × 10 − 3 mm 2 /s).…”
Section: Discussionmentioning
confidence: 99%
“…After reading the full texts of the 93 articles, we excluded 66 because 1) the aim was not to assess the diagnostic value of MRI for identification and characterization of locally recurrent prostate cancer (n = 44), 2) histopathology analysis and/or follow-up clinical analysis and imaging at 6 months post-surgery were not used as the reference standard (n = 2), 3) sufficient date were not reported for constructing 2 × 2 tables (n = 10), or 4) results were reported for combinations of imaging modalities but not for individual modalities (n = 10). Finally, 27 articles ( 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 ) fulfilled all inclusion criteria and were selected for data extraction and data analysis ( Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Study characteristics are shown in Supplementary Table 1 (in the online-only Data Supplement). Of the 27 studies, 15 were published after January 1, 2010 ( 21 22 23 24 25 30 34 37 38 39 40 42 43 44 45 ). The number of patients per study ranged widely from 11 to 176, and the number of sectors ranged from 42 to 318.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation